2015
DOI: 10.1371/journal.pone.0122248
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of Normal Range of Ankle Systolic Blood Pressure in Subjects with Normal Arm Systolic Blood Pressure

Abstract: SubjectThis study aimed to establish a normal range for ankle systolic blood pressure (SBP).MethodsA total of 948 subjects who had normal brachial SBP (90-139 mmHg) at investigation were enrolled. Supine BP of four limbs was simultaneously measured using four automatic BP measurement devices. The ankle-arm difference (An-a) on SBP of both sides was calculated. Two methods were used for establishing normal range of ankle SBP: the 99% method was decided on the 99% reference range of actual ankle BP, and the An-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(13 reference statements)
1
5
1
Order By: Relevance
“…Subgroup and sensitivity analyses by cardiovascular disease history, cardiovascular disease risk, measurement method/device and methodological quality did not sufficiently explain the observed variation, although exclusion of studies not using auscultation or a validated upper arm device did reduce some the observed heterogeneity, suggesting this may have been a contributing factor. Although age has previously been shown to affect the magnitude of arm-ankle blood pressure difference, [5] meta-regression by age revealed no such association in the present data. Other factors contributing towards the observed heterogeneity might include the blood pressure device and model used, number of readings taken and the observer making the measurement (e.g.…”
Section: Strengths and Limitationscontrasting
confidence: 92%
See 3 more Smart Citations
“…Subgroup and sensitivity analyses by cardiovascular disease history, cardiovascular disease risk, measurement method/device and methodological quality did not sufficiently explain the observed variation, although exclusion of studies not using auscultation or a validated upper arm device did reduce some the observed heterogeneity, suggesting this may have been a contributing factor. Although age has previously been shown to affect the magnitude of arm-ankle blood pressure difference, [5] meta-regression by age revealed no such association in the present data. Other factors contributing towards the observed heterogeneity might include the blood pressure device and model used, number of readings taken and the observer making the measurement (e.g.…”
Section: Strengths and Limitationscontrasting
confidence: 92%
“…[10][11][12][13][14] Few studies have set out to measure the arm-leg blood pressure difference in the general population to aid interpretation of leg measurements in clinical practice. One study by Gong et al, [5] showed in 948 patients that blood pressure was 17.4 mmHg (95% CI 16.7 to 18.1 mmHg) higher when measured in the ankle than when measured in the arm, findings which are consistent with the present review. Implications for clinical practice Current clinical guidelines pay little attention to measurement of blood pressure in the leg and there is no guidance on the most appropriate method of measurement.…”
Section: Strengths and Limitationssupporting
confidence: 92%
See 2 more Smart Citations
“…When ankle blood pressure is divided by brachial blood pressure, the single-figure outcome is known as the anklebrachial index, or ABI. For a healthy person, ankle pressure is typically higher than brachial pressure (Goldstein et al, 2014;Gong et al, 2015;Xu et al, 2010), (Note 2) and therefore the ABI is likely to be > 1.0, often in the range 1.1 to 1.3. In a person with PAD, the ABI is, at least theoretically, likely to be noticeably < 1.0, and an ABI ≤ 0.90 is often regarded as indicative of PAD (Bundó et al, 2013;Xu et al, 2010).…”
Section: The Ankle-brachial and Toe-brachial Indicesmentioning
confidence: 99%